Inhibition of Human Vascular NADPH Oxidase by Apocynin Derived Oligophenols - Mora-Pale, Mauricio (2009)
Enzymatic oxidation of apocynin, which may mimic in vivo metabolism, affords a large number of oligomers (apocynin oxidation products, AOP) that inhibit vascular NADPH oxidase. In vitro studies of NADPH oxidase activity were performed to identify active inhibitors, resulting in a trimer hydroxylated quinone (IIIHyQ) that inhibited NADPH oxidase with an IC(50) = 31 nM. Apocynin itself possessed minimal inhibitory activity. NADPH oxidase is believed to be inhibited through prevention of the interaction between two NADPH oxidase subunits, p47(phox) and p22(phox). To that end, while apocynin was unable to block the interaction of his-tagged p47(phox) with a surface immobilized biotinalyted p22(phox) peptide, the IIIHyQ product strongly interfered with this interaction (apparent IC(50) = 1.6 μM). These results provide evidence that peroxidase-catalyzed AOP, which consist of oligomeric phenols and quinones, inhibit critical interactions that are involved in the assembly and activation of human vascular NADPH oxidase.